Implementation of Decision Support System for Determination of Employee Contract Extension Method Using SAW - Sinaga, Baik Sepwanri; Riandari, Fristi (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Effect of rapid technological developments have contributed so as to provide an opportunity to study and analyze a problem. In the company of PT. Cipta Mandiri Agung Jaya, employee contract renewal process is done in less efficient. In general, the process of employee contract extension is carried out by way of division form a contract extension, has not made an assessment atupun evaluation of each employee. Through employee contract renewal process conducted so far gives a great influence to the advancement of the company. On this occasion, in view of the managerial aspects of the formulation of the problem is how to implement the SAW method in the determination of employee contract extension. How to implement a decision support system in the determination of contract extensions employees at PT. Court Of Human Self Jaya, how to design decision support systems in the SAW method using the employee contract extension programming language VB 2010 and the Microsoft Access database. The purpose was to analyze the issue formulation SAW method in the determination of employee contract extension, implementing a decision support system in the determination of contract extensions employees at PT. Court Of Human Self Jaya, pendukunng system design decisions in the SAW method using the employee contract extension programming language VB 2010 and the Microsoft Access database.